2018
DOI: 10.1634/theoncologist.2018-0045
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Recognizing and Managing Immune-Mediated Adverse Events in the Treatment of Hodgkin Lymphoma with Checkpoint Inhibitors

Abstract: This article highlights the importance of monitoring for immune-mediated adverse events (IMAEs) in patients with Hodgkin lymphoma (HL) who receive anti-programmed death-1 (anti-PD-1) therapy, with particular attention given to the recognition and management of such events. The risk of individual IMAEs differs between patients with HL and those with solid tumors, as prior treatments may predispose certain organ systems to specific IMAEs. Accurate and prompt diagnosis of IMAEs is essential for optimal management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…Clinical symptoms are not always an accurate measure of disease severity. [6][7][8][9] High-risk endoscopic features (presence of large, deep, and multiple ulcers and extensive inflammation) are associated with an increased risk of recurrence after clinical remission, frequent use of selective immunosuppressive therapy (SIT; ie, infliximab or vedolizumab), higher rates of hospitalization, and longer hospital stays. 6 We demonstrated that fecal calprotectin (FC) as a stool inflammatory marker in patients with IMDC had a strong association with endoscopic severity.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical symptoms are not always an accurate measure of disease severity. [6][7][8][9] High-risk endoscopic features (presence of large, deep, and multiple ulcers and extensive inflammation) are associated with an increased risk of recurrence after clinical remission, frequent use of selective immunosuppressive therapy (SIT; ie, infliximab or vedolizumab), higher rates of hospitalization, and longer hospital stays. 6 We demonstrated that fecal calprotectin (FC) as a stool inflammatory marker in patients with IMDC had a strong association with endoscopic severity.…”
Section: Introductionmentioning
confidence: 99%
“…Je nach AusprĂ€gung der Autoimmunreaktion kann z. B. die Gabe von Kortikosteroiden oder ein Pausieren der Medikation erwogen werden [363].…”
Section: Impfen Bei Therapie Mit Checkpoint-inhibitorenunclassified
“…Toxicities of checkpoint inhibitors. 185,186 In addition, pseudoprogression, an immunemediated tumor flare, may be observed early during checkpoint inhibitor therapy, and may provoke treatment discontinuation. For this purpose, modified criteria of response have been developed in order to account for this and avoid inappropriate premature drug discontinuation, as discussed above.…”
Section: Brentuximab Vedotin As Salvage Therapy For Relapsed/refractomentioning
confidence: 99%
“…The median time to occurrence of IMAEs is ~12 weeks (range between 1 and 112 weeks). Specific guidelines for the management of the IMAEs associated with checkpoint inhibitors have been published elsewhere 185,186…”
Section: Third-line Therapy and Beyondmentioning
confidence: 99%